2018
DOI: 10.1002/jpln.201800342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen fertilization on yield and phenolic compounds in wheat grains (Triticum aestivum L. ssp. aestivum)

Abstract: Nitrogen (N) is an important plant nutrient and is crucial for the plant growth and grain yield formation of field crops such as wheat (Triticum aestivum L. ssp. aestivum). However, little is known about the influence of N on secondary metabolites in wheat grains which are supposed to be beneficial for human health due to their antioxidant potentials. Therefore, we investigated the influence of N fertilization on plant growth and yield performance of winter wheat, as well as on total phenolic concentration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
6
26
2
Order By: Relevance
“…When analyzing the variation of polyphenol fractions in response to a rise in the N fertilization dose, hydrolysable polyphenols explain, to a large extent, the augmentation in grain total polyphenols. Our results on soluble polyphenols contrast with those of Stumpf et al [66] and Langenkämper et al [67], who reported that soluble phenolics were higher in grains of unfertilized wheat compared to fertilized plants. The increase in total polyphenols could be ascribed to the sufficient availability of phenylalanine under high N application.…”
Section: A High Nitrogen Supply Increases Total Grain Polyphenols Ducontrasting
confidence: 99%
See 2 more Smart Citations
“…When analyzing the variation of polyphenol fractions in response to a rise in the N fertilization dose, hydrolysable polyphenols explain, to a large extent, the augmentation in grain total polyphenols. Our results on soluble polyphenols contrast with those of Stumpf et al [66] and Langenkämper et al [67], who reported that soluble phenolics were higher in grains of unfertilized wheat compared to fertilized plants. The increase in total polyphenols could be ascribed to the sufficient availability of phenylalanine under high N application.…”
Section: A High Nitrogen Supply Increases Total Grain Polyphenols Ducontrasting
confidence: 99%
“…Ma et al [28] suggested that the antioxidant activity in wheat grain could be increased with an adequate N application. Our data indicate that fertilization had no effect on the anti-radical activity when considering all genotypes as a whole, in agreement with previous reports [66,70]. However, there was a genotype x treatment interaction.…”
Section: A High Nitrogen Supply Increases Total Grain Polyphenols Dusupporting
confidence: 93%
See 1 more Smart Citation
“…The level of phenolic compounds in vegetables is genotype specific though, it is greatly altered by the method and rate of N fertilization. 38…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of these studies were inconsistent. For example, Ma et al., (2015) found that increased nitrogen application increased soluble total phenolic content (TPC), while Stumpf et al., (2019) showed that soluble TPC was not significantly affected by increasing N application. Therefore, further studies are necessary to understand the effect of nitrogen on TPC.…”
Section: Introductionmentioning
confidence: 99%